First‐line treatment of double‐hit and triple‐hit lymphomas: Survival and tolerance data from a retrospective multicenter French study. Issue 3 (29th December 2020) - Laude, Marie‐Charlotte; Lebras, Laure; Sesques, Pierre; Ghesquieres, Herve; Favre, Simon; Bouabdallah, Krimo; Croizier, Carolyne; Guieze, Romain; Drieu La Rochelle, Laurianne; Gyan, Emmanuel; Chin, Roza; Aurran‐Schleinitz, Thérèse; et al.
Abstract: Historically, double or triple hit lymphoma (DHL and THL) have poor outcomes with conventional chemotherapy, but there is currently no guideline. We report the French experience in managing DHL and THL in first line using collective data on both survival and tolerance. All consecutive patients with newly diagnosis of large B‐cell lymphoma with MYC, BCL2, and/or BCL6 rearrangements, as determined by FISH between January 2013 and April 2019 were included. Based on the eligibility criteria, 160 patients were selected among the 184 patients identified. With a median follow‐up of 32 months, 2‐ and 4‐year progression free survival (PFS) rates were 40% and 28% with R‐CHOP compared with 57% and 52% with intensive chemotherapy ( P = .063). There was no difference in overall survival (OS). For advanced stages, PFS was significantly longer with intensive chemotherapy than with R‐CHOP ( P = .029). There was no impact of autologous stem cell transplantation among patient in remission. For patients with central nervous system (CNS) involvement, the 2‐year PFS and OS rate was 21% and 39%, vs 57% and 75% without CNS disease ( P = .007 and P < .001). By multivariate analysis, elevated IPI score and CNS disease were strongly and independently associated with a poorer survival, whereas treatment was not significantly associated with OS. This is the largest series reporting the treatment of DHL and THL in Europe. The PFS was significantly longer with an intensive regimen for advanced stage, but no difference in OS, supporting the need for a prospective randomized trial.